ANALYSIS, IDENTIFICATION, AND FORMULATION OF METALLOTHIONEIN EXTRACTS ON NUMEROUS VARIETIES OF PADDY 95 LEAVES - Budi Santosa; Henna Ria Sunoko (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Background: Vegetable materials, such as rice, corn, bean, and soybean have metallothionein proteins contained in their roots, stems, leaves, flowers, and fruits. Of those vegetable materials, paddy leaves have the most numerous metallotionein proteins. However, the varieties which produce the highest metallotionein proteins have not yet been found. The roles of metallothionein proteins are to bind and to detoxify heavy metals. Objectives:  to analyze, identify, and formulate the metallothionein extractscontained in numerous varieties of paddy leaves. An experimental research method. Each vegetable material of numerous varieties of paddy leaves is made into simplicia and is then processed into infusion. ELISA method is used as a technique to measure the protein level of each infusion. The metallothionein protein levels contained in numerous varieties of paddy leaves are then identified to determine the one with the highest metallothionein protein level. Extract formula is taken from the highest metallothionein level. Results :the highest metallothionein protein level is contained in paddy leaves of IR begendit (28.832 ng) while the lowest one is in paddy leaves of IR-64 SS (0.358 ng). The extracts of Paddy leaves of IR begendit with the highest protein level are then formulated into metallothionein extracts. Conclusion: Analysis on metallothionein levels of numerous varieties of paddy leaves with the highest protein level is contained in paddy leaves of IR begendit (28.832 ng) while the lowest one is in paddy leaves of IR-64 SS (0. 358 ng).Keywords: paddy leaves, metallothionein